2020
DOI: 10.1016/j.celrep.2020.107883
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Activities of Vegfr3/Flt4 and Notch1b Fine-tune Mechanosensitive Signaling during Zebrafish Cardiac Valvulogenesis

Abstract: Highlights d Flt4 is suppressed by fluid shear stress within the atrioventricular valve leaflet d Fluid shear stress activates Notch and Klf2a signaling in an independent manner d The Klf2a and Notch pathways repress Flt4 d Notch and Flt4 work antagonistically to shape the atrioventricular valve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 61 publications
1
31
0
1
Order By: Relevance
“…Also, we do not have a good understanding how this pathway is integrated with the mechanosensitive Klf2 signaling pathway, which is also regulated by blood flow during cardiac valve development ( Donat et al., 2018 ; Goddard et al., 2017 ; Steed et al., 2016 ; Vermot et al., 2009 ). Recent functional studies have demonstrated that Notch activity and Klf2 signaling within the atrioventricular endocardium are not contingent on each other ( Fontana et al., 2020 ). It remains unclear how Notch signaling and the mechanosensitive Klf2 signaling pathway are integrated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, we do not have a good understanding how this pathway is integrated with the mechanosensitive Klf2 signaling pathway, which is also regulated by blood flow during cardiac valve development ( Donat et al., 2018 ; Goddard et al., 2017 ; Steed et al., 2016 ; Vermot et al., 2009 ). Recent functional studies have demonstrated that Notch activity and Klf2 signaling within the atrioventricular endocardium are not contingent on each other ( Fontana et al., 2020 ). It remains unclear how Notch signaling and the mechanosensitive Klf2 signaling pathway are integrated.…”
Section: Resultsmentioning
confidence: 99%
“…First, we tested whether the process of Wnt pathway activation was dependent on Klf2. At 54 hpf, in double mutants of klf2a sh317 ( Novodvorsky et al., 2015 ) and klf2b pbb42 ( Fontana et al., 2020 ) (hereafter referred to as klf2 mutants), there was a complete loss of expression from the TCF reporter and ingression of atrioventricular endocardial cells into the cardiac jelly was abolished ( Figures 2 C, 2D, S2 C, S2C′, S2D, and S2D′) (100%, n = 13 embryos analyzed). Instead, the endocardium remained a luminal monolayered tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trpp2 and Trpv4 play similar roles during the formation of zebrafish atrioventricular valves (Heckel et al, 2015). In the OFT region, blood flow affected the expression of the flow-sensitive Klf2a (Vermot et al, 2009;Heckel et al, 2015;Steed et al, 2016b) and Notch (Samsa et al, 2015;Fontana et al, 2020) signaling pathways, which were strongly active in regions of highest shear stress. Yap1 was expressed in both, endothelial and smooth muscle cells surrounding the OFT.…”
Section: The Mechanosensitive Piezo1 Channel and Yap1 Signaling Modulate Outflow Tract Valvulogenesismentioning
confidence: 99%
“…A role for Vegfr3 in valvulogenesis has recently been shown by Fontana et al . 141 , 142 during cardiac development in zebrafish. Fluid shear stress acting on endocardial cells lining the atrioventricular valve leaflet independently activates Notch or Klf2a (Krüppel-like Factor 2) signalling and spatial antagonism between the Notch and Vegfr3 pathways defines atrioventricular valve morphology.…”
Section: Future Directionsmentioning
confidence: 99%